‫دور‬‫نظام‬ ‫إدارة‬ ‫البيئة‬ ‫ايزو‬ ‫في‬ ‫تطوير‬ ‫الأداء‬ ‫البيئي‬ ‫دراسة‬‫حالة‬ ‫مركب‬ ‫سيدار‬ ‫الحجار‬ - ‬‫عقبة‬ ‫حناشي; ‬‫نورهان‫ ملايكية ‬ (My University, 2018)
The objective of this study is to demonstrate the contribution of the Environmental Management System (ISO 14001) to the environmental performance of Arcelor metal, which is characterized by pollution of the environment and intensive consumption of water resources. The study was carried out in accordance with the internal documents of the institution concerned with the role of environmental management system in reducing water consumption and reducing emissions of polluting gases. The researcher also relied on the personal interview with the official responsible for implementing and following the environmental management system ISO 14000, Study. The study concluded that after the localization of the ISO 14001 environmental management system, the compound was able to: reduce polluted air emissions, control the management of water resources, better waste management